10‐Min 3D Turbo Spin Echo MRI of the Knee in Children: Arthroscopy‐Validated Accuracy for the Diagnosis of Internal Derangement. Issue 7 (24th August 2018) - Fritz, Jan; Ahlawat, Shivani; Fritz, Benjamin; Thawait, Gaurav K.; Stern, Steven E.; Raithel, Esther; Klyce, Walter; Lee, Rushyuan J.
Abstract : Background: Ten‐minute MRI of the pediatric knee can add value through increased cost‐effectiveness and decreased sedation needs but requires validation of its clinical efficacy. Purpose: To determine the arthroscopy‐based diagnostic accuracy and interreader reliability of 10‐min 3D Controlled Aliasing In Parallel Imaging Results In Higher Acceleration (CAIPIRINHA) turbo spin echo (TSE) MRI with two isotropic pulse sequences for the diagnosis of internal derangement in children with painful knee conditions. Study Type: Prospective. Subjects: Sixty children. Field Strength/Sequence: 3T, gradient echo‐based scout with automatic anatomical landmark recognition and plane prescription, 3D CAIPIRINHA SPACE TSE. Assessment: Three fellowship‐trained musculoskeletal radiologists evaluated the MRI studies independently and resolved discrepancies through consensus. Outcome variables included image quality, motion artifacts, meniscal abnormalities, anterior and posterior cruciate ligament tears, and cartilage lesions. Arthroscopic surgery served as the standard of reference, which was performed after 37 (range, 1–143) days post‐MRI. Statistical Tests: Diagnostic accuracy analysis of MRI with arthroscopic surgery as the standard of reference. Reliability analysis through calculation of interreader agreements with kappa statistics. Results: All studies were suitable for diagnostic interpretation with good‐to‐very‐good image quality ratings and little‐to‐no motion degradation ratings in the majority of cases. The sensitivities/specificities/accuracies of 3D CAIPIRINHA TSE MRI were 0.93/0.96/0.94 for 15/60 (25%) medial meniscal tears, 0.95/0.92/0.94 for 21/60 (35%) lateral meniscal tears, 0.83/1.00/0.92 for 6/60 (17%) discoid menisci, 1.00/0.98/0.99 for 16/60 (27%) anterior cruciate ligament tears, 1.0/1.0/1.0 for 2/60 (3%) posterior cruciate ligament tears, 1.00/1.00/1.00 for 5/60 (8%) osteochondritis dissecans lesions, 0.71/0.96/0.84 for 48 (13%) defects in 360 cartilage segments, and 0.85/0.97/0.91 overall. The interreader agreements were overall good‐to‐very‐good (kappa, 0.72–1.00). Data Conclusion: The clinical use of 10‐min 3D CAIPIRINHA TSE MRI of the knee in children with painful knee conditions yields an overall high arthroscopy‐validated diagnostic accuracy of 91% and good‐to‐very good interreader reliability for the diagnosis of internal knee derangements. Level of Evidence : 1 Technical Efficacy : Stage 6 J. Magn. Reson. Imaging 2019;49:e139–e151.